Health-Related Quality of Life and Related Factors in Patients With Chronic Obstructive Pulmonary Disease - Forough Rafii; Hamid Haghani; Farshad Heidari Beni (Iran University of Medical Sciences, 2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) affects different aspects of patients' life. By awareness of the quality of life and related factors of each patient, nurses can plan for and do proper care. So the present study was performed to evaluate health-related quality of life and related factors in patients with COPD. Methods: This study is a cross-sectional descriptive research that was performed on 141 patients with COPD in 2016 who referred to selected hospitals of Shahrekord University of Medical Sciences (Hajar Hospital and Ayatollah Kashani Hospital). Patients were selected and entered into the study through consecutive sampling method. The research tools included a demographic questionnaire and St George's Respiratory Questionnaire. Data were analyzed by descriptive and inferential statistical tests using SPSS V. 24.  Results: Total score of health-related quality of life in patients with COPD was 43.52; the score of symptoms, activity, and impact area were 46.24 (16.51), 52.40 (16.24), and 37.39 (15.13), respectively. It was also found that the disease stage, smoking, and comorbidity are significantly related to health-related quality of life (P = 0.001, P = 0.007, P = 0.037, respectively). Conclusion: Health-related quality of life in patients with COPD is significantly low. The stage of disease, smoking status and number of comorbidity is inversely related to the health-related quality of life. Therefore, it is better for healthcare personnel, especially nurses, to assess the health-related quality of life in patients with COPD, and thus plan for appropriate measures to improve the quality level and related factors.